Uncertainty and the dangers of monocultures in regulation, analysis, and practice - Richard Bronk; Wade Jacoby (Max Planck Institute for the Study of Societies, 2016)
Uncertainty is endemic to innovative economies and complex societies, but policymakers underestimate how damaging this is for many of their guiding assumptions. In particular, the discourse of best practice, "global solutions for global problems," and regulatory harmonization becomes questionable when there is substantial uncertainty about the future. This uncertainty makes it impossible to know what best practice will be and increases the danger that harmonization will result in highly correlated errors and shared analytical blind spots. The transnational harmonization of regulation has well-known advantages, but - especially in technocratic policy areas - also creates vulnerability to unexpected challenges by constraining how we think as well as homogenizing how we act. Faced with uncertainty, policymakers should be wary of monocultures in regulation, analysis, and practice, and instead focus on managing policy diversity to limit its costs. This paper's theoretical argument is grounded in philosophy, the history of ideas, and even biology. However, we also present empirical examples and consider some implications for political theory. – – In von Innovation geprägten Ökonomien und komplexen Gesellschaften ist Unsicherheit allgegenwärtig. Politische Akteure unterschätzen systematisch, wie sehr sie ihre Leitgedanken untergräbt. Fundamentale Unsicherheit über die Zukunft stellt insbesondere den Best-Practice-Gedanken, "globale Lösungen für globale Probleme" sowie das Leitbild regulatorischer Harmonisierung infrage. Unsicherheit macht es unmöglich, vorauszusagen, was in der Zukunft Best Practice sein wird, und erhöht die Gefahr, dass sich aus Harmonisierungsbemühungen hoch korrelierte Fehler und weitverbreitete analytische blinde Flecken ergeben. Harmonisierung von Regulierung auf transnationaler Ebene hat bekannte Vorteile, jedoch schafft sie - insbesondere in technokratischen Politikbereichen - Verletzbarkeit bei unerwarteten Anforderungen, weil sie dazu führt, dass wir eingeschränkter denken und ähnlicher handeln. Politische Akteure sollten Monokulturen in Regulierung, Analyse und Praxis mit Vorsicht gegenübertreten und die Kosten politischer Diversität regelnd eindämmen. Die theoretische Argumentation dieses Discussion Papers basiert auf Gedanken aus der Philosophie, der Ideengeschichte und selbst der Biologie. Es werden jedoch auch empirische Beispiele erläutert und Implikationen für die politische Theorie diskutiert.
Keywords: 300